2013
DOI: 10.1016/j.neuroscience.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The relation of developmental changes in brain serotonin transporter (5HTT) and 5HT1A receptor binding to emotional behavior in female rhesus monkeys: Effects of social status and 5HTT genotype

Abstract: The goal of the present study was to examine how social subordination stress and 5HTT polymorphisms affect the development of brain serotonin (5HT) systems during the pubertal transition in female rhesus monkeys. We also examined associations with developmental changes in emotional reactivity in response to a standardized behavioral test, the Human Intruder (HI). Our findings provide the first longitudinal evidence of developmental increases in 5HT1A receptor and 5HTT binding in the brain of female primates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 147 publications
(202 reference statements)
2
35
0
Order By: Relevance
“…Binding potential (BP ND ) was defined as the ratio at equilibrium of bound flumazenil to that of nondisplacable flumazenil in the tissue of each region. BP ND is a measurement used by our group previously (Embree et al , 2012) that correlates receptor density to experimental conditions (Innis et al , 2007). …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Binding potential (BP ND ) was defined as the ratio at equilibrium of bound flumazenil to that of nondisplacable flumazenil in the tissue of each region. BP ND is a measurement used by our group previously (Embree et al , 2012) that correlates receptor density to experimental conditions (Innis et al , 2007). …”
Section: Methodsmentioning
confidence: 99%
“…During the experimental period, the YNPRC Field Station acquired a Siemens P4 microPET scanner (Concorde Microsystems, Knoxville, TN, USA) with which the 5 remaining subjects were scanned using identical procedures and staff. Our previously published PET neuroimaging study that was affected by the same change in the YNPRC Imaging Center found instrumentation bias due to differences in the performance of the microPET scanners (Embree et al , 2012). In order to control for this bias we normalized data by calculating the z-distribution for each scanner and converting the mean and variation of the data from the P4 scanner to that of the Focus 220 distribution (Embree et al , 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations